Low proportions of folic acid deficiency after introduction of mandatory folic acid fortification in remote areas of northern Queensland, Australia: a secondary health data analysis. (3rd October 2019) - Slagman, Anna; Harriss, Linton; Campbell, Sandra; Muller, Reinhold; McDermott, Robyn
Abstract: Background: Australia implemented mandatory folic acid fortification of bread-making flour in 2009. Objective: To assess the impact of folic acid fortification in remote vs. regional urban areas and Indigenous vs. non-Indigenous populations in northern Queensland. Methods: Routinely collected data on folic acid measurements in remote areas and two regional urban centres in northern Queensland between 2004 and 2015 were analysed ( n = 13, 929) dichotomously (folic deficient vs. non-deficient). Results: Overall prevalence of folic acid deficiency was 3.2% (235/7282) in urban centres compared with 7.2% (480/6647) in remote areas ( p < 0.001), and 9.3% (393/4240) in the Indigenous population compared with 3.2% (273/8451) in the non-Indigenous population ( p < 0.001). Prevalence of folic acid deficiency dropped from 12.2% ( n = 481) in 2004–2008 to 1.5% ( n = 126) in 2010–2015 ( p < 0.001). This translates into a relative risk reduction (RRR) of 88%. RRR was 79% (7.2% vs. 1.5%) in urban centres, 91% (17.3% vs. 1.5%) in remote areas, 92% (20.5% vs. 1.6%) in the Indigenous population and 80% (7.4% vs. 1.5%) in the non-Indigenous population ( p < 0.001 for all). Conclusions: Substantial declines of folic acid deficiency to low and comparable proportions in former high-risk populations indicate that mandatory folic acid fortification of flour has had a population-wide benefit in northern Queensland.